Avaliação da condição de saúde oral de pacientes candidatos à cirurgia de transplante de órgãos sólidos do Hospital Universitário Walter Cantídio (HUWC/UFC) - Magalhães, Diego Peres (2009)
The replacement of diseased solid organs by healthy ones was one of the greatest advances in medicine in the last century, becoming viable only with the advent of immunosuppressive drugs, which have the ability to inhibit the response of the recipient against the graft. With the development of immunosuppressive drugs and surgical techniques, post-operative risks have become more known, being infection, mainly bacterial, one of the main reasons for the failure of the transplant. Then, microorganisms present in oral infections become a potential threat, even though they are not commonly cited as post-transplant infections promoters on literature. So, it is essential that dentists known the major oral alterations in these patients, and their needs for treatment in order to adopt a conduct to remove oral infections, and eliminating the postoperative risk. The objective of this study was to assess the oral health status and necessity of dental procedures in a group of solid organ transplant candidates. A cross sectional observational study was realized, collecting data from medical records and by an intra-oral exam, realized by a calibrated examiner. A total of 113 patients were examined, being 71 (62.83%) indicated for renal transplantation, 37 (32.74%) for hepatic and 05 (4.43%) for cardiac. The mean age was 42.13 years, and the most prevalent comorbidity was hypertension. The average DMFT index was 17.27 and the most prevalent Community Periodontal Index (CPI) was 02, found in 56 (49.6%) patients, indicating a high prevalence of gingival bleeding on probing and presence of calculus. Most patients in the study (81.32%) showed no soft-tissue lesions. Evaluating the radiographic exams, 56 (49.5%) individuals had horizontal alveolar bone resorption, and 05 (4.43%) patients had partially erupted third molars. Assessing the necessity of dental treatment, periodontal therapy was indicated in 81.5% of patients, 69.9% had restorative indication, 48.6% needed surgical procedures, and 9.7% had indication for endodontic treatment. There was no statistical difference of variables between the three transplant indications. This study concluded that the examined patients had high prevalence of oral diseases, such as caries and gingivitis/periodontitis, and, therefore, a high indication for dental treatment. Careful clinical evaluation should be performed for patients with indication for surgical procedures, minimizing the hemorrhagic risk. Moreover, there is a necessity to focus on oral health promotion within the medical services in patients with different degrees of renal, liver or heart failure, not only during the pre-transplant period, reducing the clinical complications caused by the systemic disease during dental treatment.